2021
DOI: 10.1002/mds.28718
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Aging in the Progression of Cortical Excitability in Benign Adult Familial Myoclonus Epilepsy type 1 Patients

Abstract: introduction, results, methods, comparison to the original assay, 2,5 and discussion are included as Appendix S1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The latter finding is in line with our previous study 46 showing a gradual and progressive worsening of the myoclonus overtime, which was correlated with the duration of the disease and with patients’ age. Interestingly, Neshige et al 47 suggested that at least two mechanisms might be involved in time-dependent neuronal dysfunction, such as repeat expansion causing cellular toxicity in the long-term and continuous excessive hyperexcitability state or bombardment of epileptic discharges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter finding is in line with our previous study 46 showing a gradual and progressive worsening of the myoclonus overtime, which was correlated with the duration of the disease and with patients’ age. Interestingly, Neshige et al 47 suggested that at least two mechanisms might be involved in time-dependent neuronal dysfunction, such as repeat expansion causing cellular toxicity in the long-term and continuous excessive hyperexcitability state or bombardment of epileptic discharges.…”
Section: Discussionmentioning
confidence: 99%
“…This finding seems to be in contrast with two previous cross-sectional studies that suggest a significant relationship between giant SEP and myoclonus severity 54 and aging. 47 A possible explanation may be the higher amount of ASMs that could reduce somatosensory cortex excitability in patients with more severe disease or possible concomitant cortical atrophy mechanisms in the later disease stage. However, only future longitudinal studies could address this important question.…”
Section: Discussionmentioning
confidence: 99%
“…So far, neurophysiological studies have consistently demonstrated marked and diffuse hyperexcitability of cortical areas, such as somatosensory, motor, and visual areas, likely due to excessive facilitation along with decreased inhibition of cortical excitability only partially attenuated by current ASMs. However, such cortical hyperexcitability is not strictly associated with disease severity and the size of expanded repeats 39 . The lack of correlation among cortical hyperexcitability measures and phenotypes as well as genotype would point to the intrinsic heterogeneity in clinical (i.e., phenotypic variability due to different ethnic origins), genetic (i.e., the site of the intronic expansion), as well as neurophysiological features of the disease (i.e., complex pathophysiological interaction between cortical and subcortical structures) 2 …”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory hyperexcitability, indexed by giant SEPs, seems to be associated with a more severe myoclonus 23 and older age 39 . However, such results were not entirely confirmed by the other two studies, 32,37 raising the question that not only cortical circuits but also subcortical networks might play a role in disease severity.…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 92%
See 1 more Smart Citation